Reflections on Child-Friendly Environments in Building Children's Morals and Character in the Technology Era in East Kalimantan - Saputri, Alma Elvira; Suryaningsi, Suryaningsi; Bhazar, Moh; Marwiah, Marwiah (FKIP - Universitas Riau, 2025)
Rapid technological development has brought significant changes in children's lives, including in the process of moral and character formation. East Kalimantan, as one of the provinces with a high level of digitalization, faces a major challenge in building a child-friendly environment that supports the growth and development of ethical values in the younger generation. This research aims to reflect on the role of child-friendly environments in shaping children's character amidst the technological current, emphasizing the importance of convergence between traditional and digital values. Using a descriptive-qualitative approach and content analysis of the 2024 East Kalimantan Children's Profile, this study reveals that although children's access to basic services and technology is quite high, there are still gaps in moral upbringing and digital literacy. Collaboration among families, schools, communities, and the utilization of local wisdom are important factors in creating an educational environment capable of building children's character in a balanced way in the modern era. This study provides strategic recommendations to strengthen the synergy between Child-Friendly City/Regency policies and technology-based character education rooted in local culture.